Tunable Multivalent Platform for Immune Recruitment to Lower Antigen Expressing Cancers - Lake, Benjamin P M; Wylie, Ryan G; Bařinka, Cyril; Rullo, Anthony F (Angewandte chemie. International edition, 2023)
Chemical immunotherapeutic strategies including Antibody Recruiting Molecules (ARMs - bivalent small molecules containing an antibody-binding domain (ABD) and a target-binding domain (TBD)) direct immune-mediated clearance of diseased cells. Anti-cancer ARM function relies on high tumor antigen valency, limiting function against lower antigen expressing tumors. To address this limitation, we report a tunable multivalent immune recruitment (MIR) platform to amplify/stabilize antibody recruitment to cells with lower antigen valencies. An initial set of polymeric ARMs (pARMs) were synthesized and screened to evaluate ABD/TBD copy number, ratio, and steric occlusion on specific immune induction. Most pARMs demonstrated simultaneous high avidity binding to anti-dinitrophenyl antibodies and prostate-specific membrane antigens on prostate cancer. Optimized pARMs mediated enhanced anti-cancer immune function against lower antigen expressing target cells compared to an analogous ARM.
Keywords: Prostatic Neoplasms; lidé; Antigens; antigeny; mužské pohlaví; Male; protilátky; Antibodies; nádory prostaty; fagocytóza; Phagocytosis; Humans